Stoma and peristomal complications: a rapid overview of the literature - Giorgia Chirco; Mario Antonini (Infermieristica Journal)
Complications of the stoma complex are estimated to occur in 20-70% of the ostomized population. These studies, however, appear to show contradictions in terms of definitions of the same complications, making the results of the analyses of incidence and prevalence of the phenomenon inconsistent with each other. The absence of clear and unambiguous definitions, does not allow clear evidence to be defined in science; moreover, this is reflected in the absence of a standardized clinical-care approach, which inevitably hinders the spread of an organizational and methodological culture aimed at the wellness and autonomy of the subject. In order to overcome this obstacle, different classifications of complications have been proposed throughout the years, differentiating these exclusively into macro categories, without delving into them in detail. In this regard, this review aims to clearly define, from the general to the particular, the individual complications of the stoma complex so as to provide nurses an instrument that can help them in the prevention and recognition of these.